Students' Perception of The Fondi Application in Improving Speaking and Listening Skills: Strengths and Challenges - Maudy, Devi Tania (DUTIES: Education and Humanities International Journal, 2025)
This study explores students' perceptions of the Fondi app in enhancing their English speaking and listening skills using a qualitative descriptive method. The researcher conducted interviews with two students regarding their experiences with the application. Findings indicated significant improvements in pronunciation, fluency, and confidence, along with better listening comprehension. Both students found the Fondi app very helpful for improving their English skills, noting its attractive interface and user-friendly design as key strengths. However, they also encountered challenges, including server downtime and bugs. Despite these issues, the students held a positive view of the app, recognizing its potential for facilitating real-world English practice. This study offers valuable insights into the benefits and challenges of using the Fondi app and provides recommendations for further enhancements, highlighting the importance of addressing technical issues to maximize its effectiveness in language learning.